TRAIN OF ABILITY OF CHEMISTRY TEACHERS TO MAKE OF HIGHER ORDER THINKING SKILLS LEARNING INDICATORS - Ismono Ismono (JCER (Journal of Chemistry Education Research), 2020)
Based on the 2013 Curriculum (K-13), the ability to think at a higher level is an ability that must be possessed by every teacher, especially chemistry teachers. This study aims to determine the ability of teachers in compiling indicators of achievement of learning outcomes that require high order thinking skills. This research was conducted on Chemistry teachers who took part in professional education activities of teachers in positions ranging from batch 1 to 4, in 2019. There were 40 teachers who were subject of research in Chemistry. The results obtained are based on the results of testing about 2% of teachers who have been able to compile indicators of learning outcomes based on semi-high thinking (C3). Teachers after attending training above 97% are able to compile indicators of learning outcomes based on higher order thinking (C4). The increase in n-gains increases with a high category